PENGARUH RELATIONSHIP MARKETING DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PELANGGAN ASTINET SEGMEN BISNIS PT TELKOM WITEL MAKASSAR) - Andi Nur Qalby; Abdul Razak Munir; Jusni Jusni (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
Marketing is an activity that can penetrate space and time. This study aims to determine to know the influence of Relationship Marketing and Brand Image Against Customer Loyalty at PT Telkom Witel Makassar. This type of research is causal (causal relationship research), which is trying to find the relationship of influence between relationship marketing and brand image with customer satisfaction and loyalty ASTINet users. The results showed that Relationship marketing and Brand image have positive and significant impact on customer satisfaction. Relationship marketing and Brand image also show a positive and significant influence on customer satisfaction customer loyalty. Likewise with customer satisfaction that menunukkan positive and significant influence on customer loyalty. Keywords: Relationship marketing, Brand image, customer satisfaction, customer loyalty